The alpha-L-(1----2)-trirhamnopyranoside epitope on the group-specific polysaccharide of group B streptococci. - Michon, F (1991)
A number of epitope specificities associated with the group antigen (group B polysaccharide) of group B streptococci have been identified in a polyclonal antiserum induced in rabbits by a nonencapsulated variant strain of group B streptococci. This was achieved by using a series of oligosaccharide inhibitors, obtained by both synthetic and degradative procedures, to inhibit the binding of the group B polysaccharide to the polyclonal antiserum. While the dominant epitope expressed in the antiserum was alpha-L-Rhap(1----2)alpha-L-Rhap(1----2)alpha-L-Rhap, specificities associated with alpha-L-Rhap and alpha-L-Rhap(1----3)alpha-D-Galp(1----3)beta-D-Glcp-NAc(1----4)alp ha-L-Rhap were also identified. The dominant expression of the former epitope is consistent with its terminal location on the group antigen and also with highly branched multiantennary structure of this antigen. Antibodies specific for the alpha-L-trirhamnopyranoside epitope were purified by affinity chromatography, using the synthetic trisaccharide glucitol as the hapten. Oligosaccharide inhibition studies indicate that the specificity of these antibodies is identical to that of a murine monoclonal antibody induced by the same nonencapsulated strain of group B streptococci.